RANCANG BANGUN ALAT PENGUKUR SUHU TUBUH OTOMATIS MENGGUNAKAN ARDUINO UNO - agustina, dian sri; Meilantika, Dian (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2022)
ABSTRACT The rapid development of science and technology today has created a variety of electronic equipment that is very helpful to ease human work. Electronic equipment has become a part of human life because it can help speed up or be more efficient in meeting human needs. Coronavirus Disease 2019 (Covid-19) is a new type of disease whose cause is still unknown. Covid-19 began to appear in December 2019 in the city of Wuhan, China. Often the virus is spread from person to person through droplets from the mouth and nose when an infected person coughs or sneezes, similar to the way the flu is transmitted. This research produces an Automatic Body Temperature Measuring Device Using Arduino Uno R3. By utilizing the PIR sensor to detect human movement, the Ultrasonic sensor to detect the distance between humans and the tool and the Thermopile MLX90614 temperature sensor to detect the human body temperature. Keywoard : Arduino, PIR sensor, Ultrasonic sensor and Thermopile MLX90614 temperature sensor